Sosialisasi Transformasi Digital bagi UMKM sebagai Bagian Penguatan Fondasi Ekonomi Masyarakat Kabupaten Tangerang - Basuki, Sucipto; Winanti, Winanti; Supiana, Nana; Riyanto, Riyanto; Sukriyah, Sukriyah; Fayzhall, Miyv; Goestjahjanti, Francisca Sestri; Lestari, Sri; Maesaroh, Siti; Wiyono, Nuri; Jainuri, Jainuri; Fernando, Erick (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2024)
Activities to socialize digital transformation of Micro small and Medium Enterprises in Tangerang Regency were carried out online and were attended by 497 participants with various backgrounds. There were three speakers and were guided directly by a moderator. Explained the problems and obstacles in implementing digitalization for micro small and medium enterprises, and the importance of digital transformation. This community service seminar was also filled with material about breaking down household waste into gold and beauty by the second resource person. The activity went well and was interactive between participants and resource persons. It is hoped that in the future similar activities can be carried out directly and continuously so that they can maximize the progress of Micro small and Medium Enterprises in Tangerang Regency